2006
DOI: 10.4049/jimmunol.176.1.200
|View full text |Cite
|
Sign up to set email alerts
|

The CD8+ T Cell Population Elicited by Recombinant Adenovirus Displays a Novel Partially Exhausted Phenotype Associated with Prolonged Antigen Presentation That Nonetheless Provides Long-Term Immunity

Abstract: We have previously reported that the CD8+ T cell response elicited by recombinant adenovirus vaccination displayed a delayed contraction in the spleen. In our current study, we demonstrate that this unusual kinetic is a general phenomenon observed in multiple tissues. Phenotypic analysis of transgene-specific CD8+ T cells present 30 days postimmunization with recombinant adenovirus revealed a population with evidence of partial exhaustion, suggesting that the cells had been chronically exposed to Ag. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 63 publications
10
107
2
Order By: Relevance
“…In a number of studies, vaccination with adenoviral vectors has been found to induce strong and stable CD8 + T cell and Ab responses in mice, poultry, primates, and humans (2)(3)(4)(5)(6)(7)(8). Despite the wide application of adenoviral vectors, conflicting results have been observed using similar reagents in which the virus-induced CD8 + T cell population has been characterized as anything from exhausted (9) and chronically overactivated (10) to polyfunctional and long-lived (11,12). As the reports of induction of dysfunctional T cells contrast with our own data and clinical experience, we asked the question if differences in administration route and/or dosage might account for the observed discrepancies.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…In a number of studies, vaccination with adenoviral vectors has been found to induce strong and stable CD8 + T cell and Ab responses in mice, poultry, primates, and humans (2)(3)(4)(5)(6)(7)(8). Despite the wide application of adenoviral vectors, conflicting results have been observed using similar reagents in which the virus-induced CD8 + T cell population has been characterized as anything from exhausted (9) and chronically overactivated (10) to polyfunctional and long-lived (11,12). As the reports of induction of dysfunctional T cells contrast with our own data and clinical experience, we asked the question if differences in administration route and/or dosage might account for the observed discrepancies.…”
contrasting
confidence: 49%
“…administration or peripheral overdosing shown in this study (9,10,39). The late i.v.-induced CD8 + T cells we observed bear all the markings of a dysfunctional T cell population: lower fraction of cytokine-producing cells out of total specific cells, lower IFN-g MFI, lower fraction of cells coproducing TNF-a or IL-2 and IFN-g, lower expression of IL-7R (CD127), absence of a contraction phase normally suggestive of a memory response, and an impaired ability to migrate into tissues and exert effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…We observed significant OT-I proliferation in vivo three weeks after immunization with OVA expressing lentivector 46 . Similar prolonged Ag presentation was also reported following adenoviral vector immunization 79 . Importantly, this prolonged Ag exposure correlated with potent protective immunity and in general did not prevent recall responses 16,46,59,79,80 , even though partially exhausted effector memory T cell phenotype was observed in some cases 79 .…”
Section: Prolongedsupporting
confidence: 62%
“…Similar prolonged Ag presentation was also reported following adenoviral vector immunization 79 . Importantly, this prolonged Ag exposure correlated with potent protective immunity and in general did not prevent recall responses 16,46,59,79,80 , even though partially exhausted effector memory T cell phenotype was observed in some cases 79 . It seems that the effect of prolonged Ag presentation on induced T cell responses after recombinant viral vector immunization is different from that observed in chronic viral infections where exhausted T cell responses were reported 77,81 .…”
Section: Prolongedsupporting
confidence: 62%
“…The rAd vectors were propagated using 293 cells and purified using CsCl gradient centrifugation as described previously. 45 AdhDCT encodes the full-length human DCT (also known as TRP-2), 15 AdLCMV GP expresses the sequence corresponding to residues 33-41 and 61-80 of the lymphocytic choriomeningitis virus glycoprotein. AdLacZ expresses b-galactosidase as a transgene and was used as a negative control.…”
Section: Rad and Immunizationsmentioning
confidence: 99%